2022
DOI: 10.1111/jvim.16419
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolomic profiles in dogs with chronic enteropathy

Abstract: Background Metabolic profiles differ between healthy humans and those with inflammatory bowel disease. Few studies have examined metabolic profiles in dogs with chronic enteropathy (CE). Hypothesis Serum metabolic profiles of dogs with CE are significantly different from those of healthy dogs. Animals Fifty‐five dogs with CE and 204 healthy controls. Methods A cross‐sectional study. The serum concentrations of 99 metabolites measured using a canine‐specific proton nuclear magnetic resonance spectroscopy platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…It is worth emphasizing that, in the present study, plasma Phe proportion was the only one increased in dogs with FRE. A recent study by Walker et al [ 13 ] also found greater Phe serum concentration in dogs with CEs. It has also been reported that both inflammation and infection often lead to increased levels of Phe in human patients [ 23 ] since cytokines induce a strong metabolic disruption, muscle tissue breakdown, and a catabolic state.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…It is worth emphasizing that, in the present study, plasma Phe proportion was the only one increased in dogs with FRE. A recent study by Walker et al [ 13 ] also found greater Phe serum concentration in dogs with CEs. It has also been reported that both inflammation and infection often lead to increased levels of Phe in human patients [ 23 ] since cytokines induce a strong metabolic disruption, muscle tissue breakdown, and a catabolic state.…”
Section: Discussionmentioning
confidence: 84%
“…Academic literature concerning the amino acid profile in dogs with gastrointestinal disorders is currently quite limited. Some research has been actually carried out in dogs with IRE or PLE [ 10 , 11 , 12 , 13 ]. However, current information on the amino acid profile in FRE dogs is not yet available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the loss of FAs might lead to decreased serum concentrations of FAs, which is evident in humans with IBD with decreased serum concentrations of nervonic acid, arachidonic acid, and palmitic acid [36]. Similarly, one study also reported on decreased concentrations of oleic acid, stearic acid, and saturated FAs in serum from dogs with CE using a canine-specific proton nuclear magnetic resonance ( 1 H NMR) spectroscopy platform [37].…”
Section: Discussionmentioning
confidence: 99%
“…The mean concentrations of all antioxidant biomarkers except FRAP were lower, and the oxidant markers were higher in the sera of dogs with idiopathic IBD than in healthy controls. Another study showed lower serum fatty acid concentrations in dogs with CIE than in healthy dogs, indicating dysregulation of both pro-inflammatory (arachidonic acid and cyclooxygenase pathways) and anti-inflammatory (omega-3 essential fatty acids) mediators ( 26 ). Perturbations in these mediators in the face of chronic intestinal inflammation are a recognized feature of IBD in people ( 27 ).…”
Section: Clinical Studies In Companion Animalsmentioning
confidence: 99%